261 The district of Columbia Concussion Care & Training Project: a model for youth concussion education. (1st September 2016) - Lincoln, Andrew E; Cooper, Justin B; Urbansky, Ethan A; Gioia, Gerald A; Atabaki, Shireen; McGill, Catherine; Sady, Maegan; Yochelson, Michael; Delasobera, Elizabeth; Clark, Jessica
Abstract : Background: The District of Columbia's "Concussion Protection Act of 2011" legislation requires training of youth sports program stakeholders to ensure concussion awareness and training to properly recognise, treat, and recover from a concussion. A partnership between the Children's National Medical Centre, MedStar Sports Medicine and community stakeholders was established in March 2015 to develop an infrastructure and pathways for appropriate training and documentation of compliance. Methods: The Concussion Care and Training Program (CCTP) included four priority areas: Creating Awareness, Concussion Training, Policy and Protocol Development, and Evaluation and Performance Measurement. The CCTP team implemented a combined clinical and public health approach to provide comprehensive, up-to-date training and documentation. Partnerships were established with program administrators in schools, recreation programs, and community associations to establish training needs and maximal accessibility of target audiences. Specific products were developed and disseminated across the community. Results: The CCTP performed 29 training activities to over 6000 participants. Of the 225 training participants who completed the program assessments, the largest affiliations were associated with Children's School Services (24%), Public Schools (17%), and Private Schools (14%). The most common participant roles were School Nurses (44%) and Coaches (33%). Overall, 40% of training participants were aware of the DC concussion law prior to the training. Only 41% of coaches and 32% of parents claimed to be aware of the law. Conclusions: This model program reached stakeholders of all ages and levels of youth athletes across diverse communities to provide concussion education/training, media outreach and public awareness. This model may be used by other localities to increase youth sports concussion awareness and training among community participants.